Laser spot center location by using the gradient-based and least square algorithms - Lei Xin; Lijun Xu; Zhang Cao (2013 IEEE International Instrumentation and Measurement Technology Conference (I2MTC), 2013)
A new method for laser spot center location by using the gradient-based and the least square algorithms is introduced in this paper. Compared with the traditional gravity-based algorithm, the results obtained by the proposed method are of higher accuracy. In the experiments, the dimension of the image detected by the CCD is 1024×768. The relative errors of the results were calculated in order to validate the method proposed in this paper. Comparisons of the results were made between the proposed method and the gravity-based algorithm. Results show that the proposed method is of higher accuracy for the center location and the accuracy can be improved by increasing the number of the selected points in the least square algorithm.